Synthesis and characterization of cationically and anionically modified poly(vinyl alcohol) microfibrils - Chirowodza, Helen (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2009.